Source and spatial distribution of particulate and dissolved organic matters in Iloilo city coastline, Philippines - Jumar Cadondon; Elaine Grace Fernandez; Perry Neil Fernandez; Edgar Vallar; Maria Cecilia Galvez (Journal of the Saudi Society of Agricultural Sciences)
Abstract Understanding sources and distribution of dissolved and particulate organic matter (DOM and POM) remains limited in coastal waters of Iloilo city, Philippines. Nine sampling stations near the Iloilo city coastline were used for water collection. Physico-chemical parameters (DO, pH, Temperature, EC, BOD5) were studied to determine the water quality status of the coastline based on water quality standards. High DO and BOD5 measurements were obtained in all stations except Stns 2, 3, and 4. Water samples were characterized using spectroscopy techniques (UV–visible and fluorescence), while POM was determined using particulate organic carbon and nitrogen (POC and PN) and their corresponding isotopic compositions. Weak to no correlations were observed between water quality and DOM, which suggests that DOM sources in the Iloilo city coastline are terrestrial or microbially derived. A high C/N ratio established that POM is extremely degraded and originates mainly from allochthonous sources. Some sampling stations also showed relationships with nearby land use-land cover settings in the Iloilo city coastline. Hierarchical cluster analysis identified clusters with similar water quality, DOM, and POM values, which include (a) Stn 1—Stn6—Stn 9; (b) Stn 3 – Stn 4 – Stn 7 – Stn 8; and (c) Stn 2 – Stn 5. Anthropogenic sources such as residential and commercial effluents and agricultural runoffs are possible sources of organic matter on the Iloilo city coastline.